DIGITAL MAPPING OF BUSINESS PERFORMANCE INDICATORS OF AGRICULTURAL HOLDINGS IN SERBIA - Rađenović, Žarko; Janjić, Ivana; Talić, Miljana; Đokić, Milica; Rađenović, Tamara; Boskov, Tatjana; Krstić, Bojan (Economics of Agriculture, 2025)
The capacity of new technologies to boost agricultural yields, optimize resource utilization, enhance productivity, and improve f inancial outcomes has gained significant consideration among farmers, agricultural organizations, and policymakers. Across the globe, innovative digital solutions have emerged as key catalysts for transforming and advancing the agricultural sector. Hence, this study explores the adoption of digital tools by Serbian agricultural holdings to enhance business performance and sustainability. The employed mixed-methods approach highlights disparities in digital readiness and the barriers faced by small scale farmers. Results reveal that while smartphones dominate technology use, broader adoption of digital platforms is hindered by low digital literacy, high costs, and limited infrastructure. The f indings emphasize the potential of digital agro-economic maps to optimize resource allocation, reduce costs, and improve decision making. Finally, the actions should be focused on improving digital literacy of rural population, expanding technological infrastructure, and designing policy incentives to encourage the adoption of smart agricultural practices.